Maintenance Treatment Post-transplant - Duarte, Fernando Barroso; Paton, Eduardo José Alencar (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
Disease recurrence is the most common cause of HCT failure in patients with AML,ALL and SMD and factors such as the presence of measurable residual disease before and after transplantation, stage of the disease before transplantation and the cytogenetic and molecular risk profile are factors associated with increased risk of recurrence.